Structure and luminescence properties of Ce3+ doped KBa1−x(Mg/Zn)xY(BO3)2 and K1−yNayBaY(BO3)2 phosphors evolved from cation substitution. (1st August 2017) - Xu, Rui; Liang, Yujun; Liu, Shiqi; Zhu, Yingli; Wu, Xingya; Li, Kai; Zhou, Wei
Highlights: A series of KBaY(BO3 )2 :Ce 3+ phosphor evolved from cation substitution was obtained. The blue-shift of the phosphor was analyzed in this paper. The thermal stabilities were enhanced by introducing the Mg 2+ and Zn 2+ . Abstract: The tunable blue-emitting KBa1− x (Mg/Zn) x Y0.95 (BO3 )2 :0.05Ce 3+ and K1− y Na y BaY0.95 (BO3 )2 :0.05Ce 3+ phosphors have been investigated via cation substitution of Mg 2+ /Zn 2+ for Ba 2+ and Na + for K + in KBaY(BO3 )2 host. The crystal structures, photoluminescence properties, thermal stability and the effect of Mg 2+ /Zn 2+ /Na + concentration on the luminescence characteristics were investigated in detail. The XRD analysis implied that KBa1− x (Mg/Zn) x Y(BO3 )2 solid solutions were limited, while continuous solid solution was possible in K1− y Na y BaY(BO3 )2 system. Upon the excitation at 365 nm, the emission peaks of KBa1− x (Mg/Zn) x Y0.95 (BO3 )2 :0.05Ce 3+ (0 ⩽  x  ⩽ 0.6) blue-shifted from 435 to 424 nm, and K1− y Na y BaY0.95 (BO3 )2 :0.05Ce 3+ (0 ⩽  y  ⩽ 1) blue-shifted from 435 to 427 nm with the Mg 2+ /Zn 2+ /Na + doping concentration increase. The thermal stabilities of KBa1− x (Mg/Zn) x Y0.95 (BO3 )2 :0.05Ce 3+ phosphors were enhanced from 20 °C to 200 °C by increasing the concentration of Mg 2+ and Zn 2+ . The substitution of Na + for K + led to a decrease in the proportion of 5 D- 2 F5/2 and 5 D- 2 F7/2 corresponding to the Gaussian fitting of Ce 3+ in K1− y Na y BaY0.95 (BO3 )2 :0.05Ce 3+ phosphors. At the temperature increased, the full width at half maximum of photoluminescence band of K0.8 Na0.2 BaY0.95 (BO3 )2 :0.05Ce 3+ decreased. However, the decreasing trend of FWHM became less obvious with the increasing concentration of Na + in the temperature dependent photoluminescence spectra of K1− y Na y BaY0.95 (BO3 )2 :0.05Ce 3+ phosphors.